Avaliação de novos híbridos de porta-enxertos para a laranjeira 'valência' - Simonetti, Lilian Massaro [UNESP] (2015)
The mandarin citrandarins 'Sunki' Poncirus trifoliata vs hp. Rubidoux are a new generation of rootstock for the citrus industry, which combine traits such as disease resistance, formation of small plants, high production efficiency and production of high quality fruit. The aim of this study was to evaluate citrus rootstock hybrids in competition with Lemon Tree Carnation, grafted with Valencia orange, aiming at initial evaluation of new varieties of rootstock for the citrus industry. We evaluated 59 hybrid citandarins as rootstock for Valencia orange. The variables analyzed were: canopy compatibility rootstocks, vegetative plant development, production, productivity, average fruit weight, height and diameter of the fruit, the juice yield, soluble solids (SS), titratable acidity (TA), ratio (SS/TA), technological index (TI) and maturation curve. The results were submitted to analysis of variance and compared by parametric Scott Knott test, using the statistical program Sisvar. The R-program was used to construct a dendrogram by grouping method. The SELEGEN program was used to estimate genetic parameters (heritability, variance, coefficient of variation) for all variables measured. The citrandarins influenced differently in the size of the Valencia orange canopy. Some citrandarins showed greater production (kg plant-1) and productivity (kg m-3) compared to Rangpur. All citrandarins presented fruit quality values higher than Rangpur lime. The application of dissimilarity analysis using physical and chemical characteristics of plants and fruits was effective in grouping rootstock hybrids on the characteristics that such hybrids may influence the scion variety. The clustering using the UPGMA method resulted in a dendrogram in which the hybrids were separated into four groups. The hybrid showed the best initial performance was the TSxPT 254 because it provided the scion variety, Valencia orange, desira